Alternative economic spaces - Leyshon, Andrew; Lee, Roger 1945-; Williams, Colin C. 1961- (SAGE, 2003)
This text focuses on the emergence of alternative economic geographies within developed economies and analyses the emergence of alternative economic practices within industrialized countries.